Surface wave methods for near-surface site characterization - Foti, Sebastiano (Boca Raton : CRC Press, Taylor & Francis Group, 2015)
'Surface wave methods analysis the dispersive nature of surface wave propagation in heterogeneous media to measure shear wave velocity or material damping ratio profiles, and enable earthquake site response to be assessed. This is the only comprehensive reference that provides a unified treatment of surface wave propagation, signal processing, inverse theory and the testing protocols that form the basis of modern surface wave methods. The use of these tests has increased dramatically since the 1980s, but they are too often performed and interpreted in a variety of ways that are confusing. This book answers the pressing need for a guide to the basic principles as well as outlining a set of reliable, dependable and accepted practices. It is written for geotechnical engineers, engineering seismologists and geophysicists as well as academics in these fields'--
'A SPON Press book.'
Includes bibliographical references (pages 441-458) and index.
Keywords: Surface waves (Seismology) -- Analysis; Seismic waves -- Speed; Inversion (Geophysics); Earthquake engineering